Educational Leadership as a Tool for Social Cohesion: Strategic Management Methods of Schools in Promoting a Culture of Peace and Citizenship in Lebanese Society - Saad , Huossein Mohammad (Journal of Physical Education, 2026)
This study looks into how educational leadership can help build social cohesion in public schools in Lebanon. It digs into different ways that school management can be approached, focusing on creating a culture rooted in peace and citizenship. Method A questionnaire of closed questions was applied to a stratified random sample of 217 school principals, using the descriptive-analytical method. The findings indicated that there is a positive and strong relationship (r = 0.702) between the competence of educational leadership in implementing strategic tools and the level at which social cohesion was promoted. As for current parliamentary leadership activity, it revealed good performance (average 3.40) but was short of the desirable level (3.70). Key structural barriers that were identified included.